2012
DOI: 10.1016/j.ydbio.2011.10.027
|View full text |Cite
|
Sign up to set email alerts
|

SOHLH1 and SOHLH2 coordinate spermatogonial differentiation

Abstract: Spermatogonial self-renewal and differentiation are essential for male fertility and reproduction. We discovered that germ cell specific genes Sohlh1 and Sohlh2, encode basic helix-loop-helix (bHLH) transcriptional regulators that are essential in spermatogonial differentiation. Sohlh1 and Sohlh2 individual mouse knockouts show remarkably similar phenotypes. Here we show that SOHLH1 and SOHLH2 proteins are co-expressed in the entire spermatogonial population except in the GFRA1+ spermatogonia, which includes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
177
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(195 citation statements)
references
References 57 publications
17
177
1
Order By: Relevance
“…For instance, RBPJ target genes such as Hey1 and Heyl were upregulated in Sertoli cells, as expected; in germ cells, Nanos2, a gene that suppresses meiosis, 54 was downregulated, and genes that are expressed at the beginning of or during meiosis, such as Stra8 and Rec8, 55,56 were all upregulated (GSE37073). Furthermore, in accord with the observation that germ cell differentiation had taken place, a significant decrease in Pou5f1 (a marker for undifferentiated spermatogonia) 57 and a significant increase in Sohlh2 (a marker for differentiating spermatogonia) 58 were also found in these mutant germ cells. Our molecular analyses demonstrated that these effects correlated with a downregulation of Sertoli cell-specific factors that are essential to maintaining the undifferentiated state of germ cells.…”
Section: Amh-nicd1 Mouse Modelsupporting
confidence: 80%
“…For instance, RBPJ target genes such as Hey1 and Heyl were upregulated in Sertoli cells, as expected; in germ cells, Nanos2, a gene that suppresses meiosis, 54 was downregulated, and genes that are expressed at the beginning of or during meiosis, such as Stra8 and Rec8, 55,56 were all upregulated (GSE37073). Furthermore, in accord with the observation that germ cell differentiation had taken place, a significant decrease in Pou5f1 (a marker for undifferentiated spermatogonia) 57 and a significant increase in Sohlh2 (a marker for differentiating spermatogonia) 58 were also found in these mutant germ cells. Our molecular analyses demonstrated that these effects correlated with a downregulation of Sertoli cell-specific factors that are essential to maintaining the undifferentiated state of germ cells.…”
Section: Amh-nicd1 Mouse Modelsupporting
confidence: 80%
“…In vitro experiments further showed that SOHLH1 and SOHLH2 can independently and cooperatively bind a bHLH binding site containing probe designed on discrete sequences of the Kit transcriptional regulatory regions. Finally, by chromatin immunoprecipitation (ChIP) analysis, SOHLH1 was found to occupy discrete bHLH binding site containing regions within the Kit promoter in spermatogonia chromatin (Barrios et al, 2012;Suzuki et al, 2012). Moreover, the human SOHLH1 gene, but not a deletion mutant associated to non-obstructive azoospermia, was previously shown to transactivate the human Kit promoter in transfection experiments (Choi et al, 2010).…”
Section: Transcription Factors Controlling Kit Expression In the Germmentioning
confidence: 99%
“…Good candidates were two bHLH transcription factors specifically expressed in germ cells, SOHLH1 (Spermatogenesis and Oogenesis HLH1) and SOHLH2. Both SOHLHs have been involved in the differentiation of spermatogonia and oocytes (Ballow et al, 2006a;Ballow et al, 2006b;Hao et al, 2008;Pangas et al, 2006;Toyoda et al, 2009;Suzuki et al, 2012). In the male, deletion of each transcription factor leads to the disappearance of KIT-expressing spermatogonia in the prepuberal testis, whereas, in the female, both SOHLH1 and SOHLH2 ablations are responsible of oocyte loss in the neonatal ovary.…”
Section: Transcription Factors Controlling Kit Expression In the Germmentioning
confidence: 99%
“…A number of transcriptional regulators also have been shown to play essential roles in controlling spermatogonial differentiation, including the basic helix-loop-helix (bHLH) proteins SOHLH1 and SOHLH2, and the DMRT protein DMRT1 (Ballow et al, 2006;Hao et al, 2008;Matson et al, 2010;Suzuki et al, 2012). DMRT proteins are transcription factors that bind DNA via the DM domain, a structurally distinct class of zinc-finger motif (Erdman and Burtis, 1993;Zhu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%